Pharmacological Inactivation of CatSper Blocks Sperm Fertilizing Ability Independently of the Capacitation Status of the Cells: Implications for Non-hormonal Contraception - Curci, Ludmila; Carvajal, Guillermo; Sulzyk, Valeria; Gonzalez, Soledad Natalia; Cuasnicú, Patricia S. (Frontiers in Cell and Developmental Biology, 2021)
CatSper, the main sperm specific Ca2+ channel, plays a key role in mammalian fertilization and it is essential for male fertility, becoming an attractive target for contraception. Based on this, in the present work we investigated the effects of CatSper inactivation on in vitro and in vivo sperm fertilizing ability and the mechanisms underlying such effects. Exposure of cauda epididymal mouse sperm to different concentrations (1-20 μM) of the potent CatSper inhibitor HC-056456 (HC) during in vitro capacitation showed no effects on sperm viability but significantly affected Ca2+ entry into the cells, progressive motility, protein tyrosine phosphorylation, induced acrosome reaction and hyperactivation as well as the sperm ability to in vitro fertilize cumulus oocyte complexes and zona-free eggs. Whereas the presence of HC during gamete co-incubation did not affect in vitro fertilization, exposure of either non-capacitating or already capacitated sperm to HC prior to gamete co-incubation severely reduced fertilization, indicating that sperm function is affected by HC when the cells are incubated with the drug before sperm-egg interaction. Of note, insemination of HC-treated sperm into the uterus significantly or completely reduced the percentage of oviductal fertilized eggs showing, for the first time, the effects of a CatSper inhibitor on in vivo fertilization. These observations, together with the finding that HC affects sperm fertilizing ability independently of the sperm capacitation status, provide further insights on how CatSper regulates sperm function and represent a solid proof of concept for developing a male/female non-hormonal contraceptive based on the pharmacological blockage of CatSper activity..